Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

Fast Multiobjective Gradient Methods with Nesterov Acceleration via Inertial Gradient-Like Systems - Sonntag, Konstantin; Peitz, Sebastian (Journal of Optimization Theory and Applications)
We derive efficient algorithms to compute weakly Pareto optimal solutions for smooth, convex and unconstrained multiobjective optimization problems in general Hilbert spaces. To this end, we define a novel inertial gradient-like dynamical system in the multiobjective setting, which trajectories converge weakly to Pareto optimal solutions. Discretization of this system yields an inertial multiobjective algorithm which generates sequences that converge weakly to Pareto optimal solutions. We employ Nesterov acceleration to define an algorithm with an improved convergence rate compared to the plain multiobjective steepest descent method (Algorithm 1). A further improvement in terms of efficiency is achieved by avoiding the solution of a quadratic subproblem to compute a common step direction for all objective functions, which is usually required in first-order methods. Using a different discretization of our inertial gradient-like dynamical system, we obtain an accelerated multiobjective gradient method that does not require the solution of a subproblem in each step (Algorithm 2). While this algorithm does not converge in general, it yields good results on test problems while being faster than standard steepest descent.

A Descent Method for Nonsmooth Multiobjective Optimization in Hilbert Spaces - Sonntag, Konstantin; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Volkwein, Stefan (arXiv:2402.06376)
The efficient optimization method for locally Lipschitz continuous multiobjective optimization problems from [1] is extended from finite-dimensional problems to general Hilbert spaces. The method iteratively computes Pareto critical points, where in each iteration, an approximation of the subdifferential is computed in an efficient manner and then used to compute a common descent direction for all objective functions. To prove convergence, we present some new optimality results for nonsmooth multiobjective optimization problems in Hilbert spaces. Using these, we can show that every accumulation point of the sequence generated by our algorithm is Pareto critical under common assumptions. Computational efficiency for finding Pareto critical points is numerically demonstrated for multiobjective optimal control of an obstacle problem.

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

“A Short Introduction to the Film Glove and Touch Studies.” - Kraft, Kerstin